Synthesis and Quantum Chemistry Study of Amide-type Acyclic Polyether - Wei, Qing-Li; Wen, Yong-Hong; Zhang, Shu-Sheng; Liu, Nian; Liang, Juan (Asian Journal of Chemistry, 2010)
Four kinds of amide-type acyclic polyether ligands were synthesized and the crystal structures of the ligands were determined by X-ray diffraction. The electronic structures of the amide-type acyclic polyether ligands have been studied by using the density functional theory of the quantum chemistry program package Gaussian 98. All the geometry of the ligands and the reactants have been optimized at the level of B3LYP/6-31G. The analysis of Mulliken populations and the main composition and proportion of the frontier orbitals indicated that these acyclic polyethers should have some capabilities to coordinate with metal ions and the active site of each ligand has been confirmed elementarily. Compound 4 was forecast as the ligand with a higher potency to coordinate with metal ions than others from the result of comparing the energy difference (ELUMO – EHOMO) of these compounds.